Dry matter productivity of the dwarf and normal elephantgrasses as affected by the planting density and cutting frequency - Muhammad Mukhtar (Indonesian Center for Animal Research and Development (ICARD), 2006)
The effects of planting density and cutting frequency on dry matter productivity were compared in two years following establishment among dwarf varieties (early-heading, DE and late-heading, DL) and normal varieties, Wruk wona (Wr) and Merkeron (Me), in the southern part of Kyushu, Japan. The planting densities examined for Wr, DE and DL were high (16 plants/m2, 25 cm × 25 cm of spacing), medium (8 plants/m2, 50 × 25 cm), and low (4 plants/m2, 50 cm × 50 cm), while for Me was only medium. The cutting frequency was three times with 60-day intervals in 2002 and two times with 90-day intervals in 2003. Irrespective of the planting densities, dwarf varieties were higher in tiller number, leaf area index and percentage of leaf blade (PLB) than those of normal varieties, but lower in plant height and total dry matter weight at all planting densities in both years. With the increase in planting density, annual herbage dry matter yield (HDMY) increased. The annual HDMY was higher in 2002 (cut twice) than that in 2003 (cut three times), and the difference in annual HDMY between the dwarf and normal varieties decreased by planting at high density and cut twice. Even though, the dry matter productivity was higher in the normal varieties than in the dwarf varieties at any planting density and cutting frequency, DL tended to show a stable productivity with high PLB irrespective of planting density and cutting frequency. Key Words: Cutting Frequency, Dry Matter Productivity, Dwarf Elephantgrass, Normal Elephantgrass and Planting Density